2007
DOI: 10.3354/ame047253
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and seasonal dynamics of diatom biofilms and associated grazers in intertidal mudflats

Abstract: The composition and seasonal dynamics of biofilm-associated eukaryotic communities were analysed at the metre and kilometre scale along a salinity gradient in the Westerschelde estuary (The Netherlands), using microscopy and a genetic fingerprinting technique (PCR-DGGE). Microphytobenthic biomass, measured as chlorophyll a (chl a), varied seasonally over 2 orders of magnitude, being highest in spring. Communities were dominated by epipelic diatoms, in particular by members of the genus Navicula. In spring, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 61 publications
(67 reference statements)
4
39
2
Order By: Relevance
“…We detected large decreases in diatom abundance and biomass in the presence of grazers, supporting other studies that demonstrated strong grazer impacts on diatom biomass (Hagerthey et al, 2002; Sahan et al, 2007). We also detected decreases in average diatom length in snail addition treatments, suggesting that snails are capable of consuming larger (>25 μm long) diatoms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We detected large decreases in diatom abundance and biomass in the presence of grazers, supporting other studies that demonstrated strong grazer impacts on diatom biomass (Hagerthey et al, 2002; Sahan et al, 2007). We also detected decreases in average diatom length in snail addition treatments, suggesting that snails are capable of consuming larger (>25 μm long) diatoms.…”
Section: Discussionsupporting
confidence: 90%
“…Other biotic and abiotic factors, such as salinity (Sahan et al, 2007), sediment grain size (Watermann et al, 1999), or the non-trophic impacts of higher consumers (Armitage and Fong, 2006) can disrupt these interactions and decouple grazing and enrichment effects on benthic microalgal communities. We detected few interactions between snail and nutrient addition treatments, possibly because of high background nutrient levels or strong herbivore pressure.…”
Section: Discussionmentioning
confidence: 99%
“…After the oysters were killed, MPB patches regularly showed a more complex and disaggregated structure instead of the regular patch shape usually observed. Variations in bathymetry, tidal dynamics, sediment type, irradiance and grazing had already been documented as factors structuring MPB spatio-temporal distribution (Brotas et al, 1995;Méléder et al, 2003;Sahan et al, 2007;Ribeiro et al, 2013). However, to date there are only a few studies which have explicitly investigated the influence of nearby macrobenthic communities on MPB dynamics (Dame, 1993;Méléder et al, 2003Newell, 2004;Engel et al, 2017).…”
Section: Oyster Reefs Influence On Mpb Biofilm Developmentmentioning
confidence: 99%
“…Fortunately, the high speed of MPB migration allowed us to work with satellite data that could be obtained during most of the low-tide period. It should also be kept in mind that while MPB biomass at the surface of the sediment can change as a result of vertical migration (Brouwer and Stal, 2001;Chennu et al, 2013), it can also be affected by other exogenous factors such as temperature and irradiance (Saburova and Polikarpov, 2003;Jesus et al, 2009;Coelho et al, 2011). A better understanding of these temporal dynamics requires high spatial and temporal resolution RS data.…”
Section: Rs As a Tool To Investigate Multi-scale Ecological Processesmentioning
confidence: 99%
“…In undisturbed sediments, microphytobenthos such as diatoms tend to form relatively stable structures like diatom films (Holland et al 1974, Sahan et al 2007), which in turn support a rich and abundant protistan community (Hamels et al 2001, Sahan et al 2007). The permanent reworking of the sediment poses a shear stress, which inhibits the formation of such biofilms.…”
Section: Physical Stressmentioning
confidence: 99%